Análisis de los aspectos legales esenciales de la propiedad intelectual e industrial en Venezuela - Peñaranda, Héctor R. (Nómadas. Critical Journal of Social and Juridical Science, 2011)
The intellectual rights are seeing like the common heap of the society and with the technological advance, the communications and the global development they acquire universal contours for the benefit of the humanity. So that It is necessary a State control to protect these rights.